Ultra-high vacuum investigations of atomic layers at low temperatures - Grazhulis, V. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
Low-temperature (10-300K) investigations of Ag atomic overlayers on Ge (111), Si (111), and InSb (110) surfaces by means of different surface science techniques are briefly reviewed. It is shown that Ag monolayers can show very different behavior on different substrates. In the case of InSb (110) new type of Ag an be formed. Resent achievements in the development of ultra-high vacuum techniques are also briefly discussed.